Exploring the Linkages between Remittances, Economic Growth and Poverty: Empirical Evidence from Pakistan - Bashir, Shiza (The Economics and Finance Letters, 2020)
This research mainly focuses on the impacts and implications of foreign remittances and how they affect the growth and poverty reduction in an economy. It further highlights the importance that remittances have on the improvement of the living conditions and standards in Pakistani. In order to achieve this target, we retrieved time-series data from the WDI, from the year 1980 till 2017. The econometric technique ARDL is applied which shows that there is a favorable relation among the variables. Our empirical findings suggest that the recipient country shows a positive trend in economic growth as an aftermath of increased remittances. Moreover, it proves that remittances have a notable influence on the reduction of poverty and boosting living standards in Pakistan economy. This ultimately leads to improving the socio-economic condition of the country in question. Results and findings, if used efficiently, have great potential policy implications for policymakers in the field of remittances.